Proceedings of the Ninth International Congress on Science and Skiing (ICSS) - Saalbach/Hinterglemm March 2023 - Thomas Leonhard Stöggl; Hans-Peter Wiesinger; Hermann Schwameder (Bern Open Publishing, 2024)
Winter sports play a crucial role across individuals of all age groups, athletes or recreational enthusiasts with considerable health, economic and touristic importance. Besides these benefits challenges arise as equipment safety, athlete preparation to perform on highest level and prevent from injury, rehabilitation, sustainability, equipment etc. In this context, the International Congress on Science and Skiing (ICSS) has been a regular pivotal gathering for over 20 years. ICSS was hosted first time in 1996 in St. Christoph am Arlberg and celebrated in 2023 the 9th conference in Saalbach/Hinterglemm. The ICSS gathers winter sports experts around the world with up to 250 participants from more than 15 nations. Selected contributions were critically reviewed to be published Current Issues of Sport Science. The special issue demonstrates the broad spectrum of contributions in all fields and disciplines in winter sports.